The impacts of gas impurities on the minimum miscibility pressure of injected CO2-rich gas–crude oil systems and enhanced oil recovery potential - Abouzar Choubineh (KeAi Communications Co., Ltd., 2018)
Abstract An effective parameter in the miscible-CO2 enhanced oil recovery procedure is the minimum miscibility pressure (MMP) defined as the lowest pressure that the oil in place and the injected gas into reservoir achieve miscibility at a given temperature. Flue gases released from power plants can provide an available source of CO2, which would otherwise be emitted to the atmosphere, for injection into a reservoir. However, the costs related to gas extraction from flue gases is potentially high. Hence, greater understanding the role of impurities in miscibility characteristics between CO2 and reservoir fluids helps to establish which impurities are tolerable and which are not. In this study, we simulate the effects of the impurities nitrogen (N2), methane (C1), ethane (C2) and propane (C3) on CO2 MMP. The simulation results reveal that, as an impurity, nitrogen increases CO2–oil MMP more so than methane. On the other hand, increasing the propane (C3) content can lead to a significant decrease in CO2 MMP, whereas varying the concentrations of ethane (C2) does not have a significant effect on the minimum miscibility pressure of reservoir crude oil and CO2 gas. The novel relationships established are particularly valuable in circumstances where MMP experimental data are not available.